Survey of churches damaged by the 2012 Emilia-Romagna earthquake sequence - Esmeralda Paupério (2012)
This report presents an overview of the damage that was observed in fourteen churches that were hit by the May 2012 Emilia-Romagna earthquake sequence. The data was collected over the course of a two-day reconnaissance mission that took place on the 9th and 10th of July 2012, and that involved researchers from the Civil engineering Department of the Faculty of Engineering of the University of Porto and of the University of Aveiro, both institutions from Portugal. It is noted that the current report only focusses the post-seismic damage assessment of churches and does not address the cultural and artistic losses associated to movable or immovable heritage. Furthermore, it is also referred that since the reconnaissance mission took place after the major earthquakes of the 20th and the 29th of May, the source of the reported damages is not assigned to a particular event and must be seen as the cumulative effect of several ground motions.